Study on secondary metabolites of endophytic fungus Diaporthe sp. AC1 induced by tryptophan analogs - Zhang, Shikai; Xu, Qing; Ji, Changbo; Han, Xiaoyu; Zhou, Yang; Liang, Chao; Ma, Linran; Sun, Weijian; Li, Yanling; Yang, Zhengyou; Zhao, Fengchun; Tian, Yuan (Frontiers in Microbiology, 2023)
Small molecule-induced fermentation of the endophytic fungus Diaporthe sp.AC1 originated from Artemisia argyi was executed to investigate its secondary metabolites. It was fermented in a culture medium containing 5-hydroxytryptophan(5-HTP), 1-methyl-L-tryptophan (1-MT), and tryptamine (TA), respectively. The antibacterial activities of crude extracts against pathogenic bacteria and pathogenic fungi were determined by using the Oxford cup method, while the cytotoxicity of crude extracts against cancer cells was determined by using the MTT method. The results showed that the secondary metabolites of Diaporthe sp. AC1 induced by 1-MT exhibited optimal antibacterial activity and tumor cytotoxicity. The induction conditions of 1-MT were optimized, and the antibacterial activities and tumor cytotoxicity of crude extracts under different induction conditions were investigated.As indicated, the optimal moment for 1-MT addition was before inoculation and its optimal concentration was 0.25 mM. Under these conditions, Diaporthe sp. AC1 was fermented and approximately 12 g of crude extracts was obtained. The crude extracts were then separated and purified to acquire nine monomer compounds, including three new compounds (1-3) and six known compounds (4-9). The antibacterial activities of the compounds against pathogenic bacteria and pathogenic fungi were investigated by using the microdilution method, while their cytotoxicity against cancer cells was analyzed by using the MTT method. The results demonstrated that Compound 1 exhibited moderate antibacterial activities against Verticillium dahlia, Fusarium graminearum, and Botrytis cinerea, as well as a low inhibitory activity against Listeria monocytogenes. Nevertheless, Compound 1 showed significant cytotoxicity against five cancer cells, with IC50 ranging from 12.26 to 52.52 μM.Compounds 2 and 3 exhibited negligible biological activity, while other compounds showed detectable inhibitory activities against pathogenic bacteria and cancer cells.